THU0045 Targeting Inflammation in SjÖGren's Syndrome – Novel Micrornas as Potential Therapeutics. (10th June 2014) - Ní Gabhann, J.; Pilson, Q.; Jefferies, C.A.; Murphy, C.C.
Abstract : Background: Sjögren's syndrome (SS) is a systemic autoimmune disorder characterized by inflammation that affects mucous membranes particularly those of the exocrine glands, causing dry eyes and dry mouth. The exocrine glands become infiltrated with lymphocytes resulting in severe damage to both the salivary glands and the lacrimal glands. Additionally patients can develop a wide range of other systemic inflammatory manifestations. SS patients have significantly increased risk of developing non-Hodgkin's lymphoma and severe pulmonary fibrosis. Previous investigations have suggested that dysregulated systemic inflammation contributes to the development and pathogenesis of SS. Current therapies fail to address the underlying inflammatory component of this disease, as well as failing to predict those that will develop serious complications. Objectives: This study aimed to investigate potential mechanisms responsible for over production of pathogenic cytokines in SS patients. Recently non-coding microRNA (miR) species have been shown to regulate inflammation and altered miR expression profiles have been reported for SS patients, however the exact function of these miRs is unknown. Methods: Peripheral blood mononuclear cells and serum were prepared from whole blood taken from both healthy controls and primary Sjögren's syndrome patients. Gene induction and micro-RNA expression were analysed by real-time PCR. Cytokine levels were determined by ELISA. Results: We observed significantly enhanced expression of the pro-inflammatory micro-RNA, miR-155 and significantly reduced levels of the IL-10 promoting miR, miRNA-21 compared to healthy controls. In keeping with this altered pattern of miR expression we observed increased serum levels of pro-inflammatory cytokines (IL-6, IL-8 and TNF-a) as well as the Th17 promoting cytokine, IL-23p19. Altered expression of previously identified targets of miR-155 (SHIP-1, SOCS1 – potent anti-inflammatory regulators) and miR-21 (IL12p35 and PDCD4, positive regulators of inflammation) was also observed. Significantly the observed reduction in expression of SOCS1 was found to correlate with increased peripheral TNF-a and IL-8 levels in pSS patients. Conclusions: Our data suggest that abnormal expression or regulation of miRs and consequently miR regulated genes in innate immunity may contribute to the initiation and progression of SS. Thus we have demonstrated a functional link between altered miR expression and over production of pathogenic cytokines in SS patients. References: Delaleu N et al. 2005 Eur J Oral Sci 113: 101-113. Low HZ et al. Arthritis Res Ther 2011, 13(3):218. Fox RI et al. J Immunol 1994, 152(11):5532-9. Deshmukh US et al. J Oral Pathol Med 2009, 38(1):42-7. Moutsopoulos NM et al. Ann Rheum Dis 2008, 67(10):1437-43. Garcic-Carrasco M et al. Clin Exp Rheumatol 2001, 19(4):411-5. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3747